2020
DOI: 10.1021/acs.jpclett.0c01390
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Recognition in Viral RNA Necessitates Rare Conformational Transitions

Abstract: Ribonucleic acids (RNAs) are conformationally flexible molecules that fold into three-dimensional structures and play an important role in different cellular processes as well as in the development of many diseases. RNA has therefore become an important target for developing novel therapeutic approaches. The biophysical processes underlying RNA function are often associated with rare structural transitions that play a key role in ligand recognition. In this work, we probe these rarely occurring transitions usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 53 publications
(77 reference statements)
0
23
0
Order By: Relevance
“…In this regard, RNA motifs from the HIV genome [26][27][28] serve as good model systems [29][30][31] to understand the viral RNA recognition mechanism by lab-evolved proteins. The HIV-1 trans-activation response element RNA (TAR; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, RNA motifs from the HIV genome [26][27][28] serve as good model systems [29][30][31] to understand the viral RNA recognition mechanism by lab-evolved proteins. The HIV-1 trans-activation response element RNA (TAR; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…We also observed that the flipping of a single base caused local rearrangements in the neighboring bases which then resulted in global structural transitions in a stem-loop of the dsRNA. We suggest that the approaches described in this work are potentially applicable to other RNA/ligand systems, for example, conformational transitions coupled to binding of a ligand molecule in an RNA element from HIV-1, as reported in our previous work …”
Section: Discussionmentioning
confidence: 56%
“…We suggest that the approaches described in this work are potentially applicable to other RNA/ligand systems, for example, conformational transitions coupled to binding of a ligand molecule in an RNA element from HIV-1, as reported in our previous work. 67 ■ ASSOCIATED CONTENT * sı Supporting Information…”
Section: Identification Of Other Potential Cvs All Of the Predefined ...mentioning
confidence: 99%
“…According to the protocol developed by Jensen et al (110), we used the exponential averaging of the Jarzynski's equality (111) to estimate the PMF along the reaction coordinate from work distributions obtained using SMD simulations (105,112). We have previously demonstrated the utility of this approach for studying RNA-ligand interactions (102). The exponential averaging expression is as follows:…”
Section: Potential Of Mean Force Calculationmentioning
confidence: 99%